Arduino Advances in Web of Science. A Scientific Mapping of Literary Production - Lopez-Belmonte, Jesus; Marin-Marin, Jose-Antonio; Soler-Costa, Rebeca; Moreno-Guerrero, Antonio-Jose (IEEE access, 2020)
Technology and computer learning have acquired a great projection in the field of education. Arduino arises from current technological innovations with the intention of promoting a new approach to learning through machines. The objective of this research is to analyze the evolution of the Arduino concept in the scientific literature. To achieve this aim, a bibliometric methodology based on scientific mapping and an analysis of co-words has been used. The scientific production of Arduino indexed in Web of Science has been analyzed. We have worked with an analysis unit of 346 documents. The results of this research show that the scientific production on Arduino in the field of education starts in 2010 until today. The communications in the congresses to present the results of the investigations developed are the most used means of diffusion. The National University of Distance Education and the Lucian Blaga University of Sibiu are particularly noteworthy. The authors with more scientific production in this field of study are Bogdan, M. and Castro, M. It is significant that the collection of studies on this subject is carried out, above all, by EDULEARN Proceedings and INTED Proceedings. It can be concluded that the field of study on Arduino in the educational field is relatively recent, so that today, the basis for scientific research is still being established. However, the most relevant aspects in this field of study are physic experiments, computational thinking and computer-based learning.